Treatment of oral leukoplakia with CO2 laser (10,600 nm): analysis of 37 cases - CAMPOS,Wladimir Gushiken de (2022)
Abstract Oral leukoplakia is a potentially malignant disorder, defined as a white plaque that cannot be diagnosed as another known disease or disorder, and has an increased risk of malignancy. The aim of the present study was to evaluate the results of CO2 laser treatment in a well-defined cohort of patients with oral leukoplakia in order to identify the occurrence of clinical outcomes of relapse, resolution, or malignancy after treatment. The study group comprised 37 patients. Before treatment, clinical photographs and incisional biopsies were obtained in all cases. In addition, the post-treatment results were documented using photographs. Evaluation of treatment results was performed by an independent researcher who had not performed the surgery. The minimum, maximum, and mean values of continuous variables were calculated. Statistically significant relationships were tested using the Cox regression analysis. A survival curve was constructed according to the Kaplan–Meier method to analyze the malignant transformation and recurrence of oral leukoplakia. The clinical outcomes analyzed were resolution, recurrence, and malignancy. The mean follow-up period was 36 months (range, 6–239 months). In 13/37 patients, leukoplakia recurred between 6 and 93 months (mean, 38.2 months). In 8/37 patients, a malignant transformation occurred (mean, 50.6 months). In 16/37 patients, lesion resolution occurred. No risk factor was statistically significant for malignancy or recurrence of lesions. The treatment of the lesions by CO2 laser was efficient in the removal of the lesions; however, it did not avoid the clinical outcomes of recurrence or malignancy.